Diplocephalus komposchi n. sp., a new species of erigonine spider (Araneae, Linyphiidae) from Austria - Milasowszky, Norbert; Bauder, Julia; Hepner, Martin (Zootaxa, 2017)
The erigonine cladistic analyses of Hormiga (2000) and Miller & Hormiga (2004) demonstrated unambiguous support for a sister-taxon relationship between the genera Diplocephalus and Savignia. These genera, in addition to others, are commonly placed in the Savignia-group. Although the Savignia-group is not monophyletic as it was originally circumscribed by Millidge (1977), it contains a monophyletic core of genera that has been supported in various cladistic analyses, starting with Hormiga (2000). According to the most recent phylogenetic study (Frick et al. 2010), a clade within the Savignia-group included Diplocephalus along with Araeoncus, Dicymbium, Erigonella, Glyphesis and Savignia. Frick et al. (2010) included three Diplocephalus species – cristatus, latifrons and picinus – in their cladistic analyses. While D. latifrons and D. picinus were found to be the most basal species of the Savignia-group, D. cristatus was the most distal one.